2000
DOI: 10.1590/s0102-69092000000500003
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion and public policies: theoretical dilemmas and political alternatives

Abstract: The article discusses the consequences of the present pattern of urban violence on the sociability and policies in popular neighborhoods of Rio de Janeiro from the perspectives and political proposals put forth by the anti-utilitarian thought of some European social scientists. Initially, it discusses the suggestions for active citizenship or for social life participation in several ways and levels for the remaking of the nation state. Then, it analyses the ambiguities and paradoxes of reciprocity in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Numerous epidemiological studies have demonstrated the role of social inequalities in the distribution of disease and mortality (Centerwall, 1974;Onwuachi-Saunders and Hawkins, 1993;Soares, 1996;Strohmeier, 1998;Zaluar, 2000). In the underdeveloped world, where vast metropolitan peripheries suffer simultaneously from poverty, low educational levels, and lack of social services, this inequality assumes dramatic proportions.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous epidemiological studies have demonstrated the role of social inequalities in the distribution of disease and mortality (Centerwall, 1974;Onwuachi-Saunders and Hawkins, 1993;Soares, 1996;Strohmeier, 1998;Zaluar, 2000). In the underdeveloped world, where vast metropolitan peripheries suffer simultaneously from poverty, low educational levels, and lack of social services, this inequality assumes dramatic proportions.…”
Section: Article In Pressmentioning
confidence: 99%
“…Reform of the law enforcement and legal system are also essential (Minayo, 1994). In the words of Alba Zaluar (2000), which are shared by many of those reflecting on violence and society in Brazil, ''A fair, democratic country cannot exist without such policies. In an exclusionary social context, penalty is imposed in terms of access, not only to material goods, but also to employment, health, justice, education, leisure, and personal development.…”
Section: Article In Pressmentioning
confidence: 99%